2021
DOI: 10.1037/edu0000494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial training on mathematics in first and sixth grade children.

Abstract: A pretest-training-posttest design assessed whether training to improve spatial skills also improved mathematics performance in elementary-aged children. First grade students (mean age ϭ 7 years, n ϭ 134) and sixth grade students (mean age ϭ 12 years, n ϭ 124) completed training in 1 of 2 spatial skills-spatial visualization or form perception/VSWM-or in a nonspatial control condition that featured language arts training. Spatial training led to better overall mathematics performance in both grades, and the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…Beyond correlational evidence, there is evidence that spatial visualization has a causal effect on these numerical skills. Cognitive training studies have demonstrated transfer of gains from spatial visualization training (measured using spatial transformation tasks) to numerical competencies including: calculation performance (Cheng & Mix, 2014; Gilligan, Thomas, & Farran, 2019; Mix, Levine, Cheng, Stockton, & Bower, 2020); symbolic number comparison (Hawes, Moss, Caswell, Naqvi, & MacKinnon, 2017); word problems (Lowrie et al, 2019; Mix et al, 2020); and place value (Mix et al, 2020). For example, it has been found children who were trained in spatial transformation demonstrated significant improvements in accuracy on a range of number‐based measures including Missing Term Problems (Mix et al, 2020).…”
Section: Spatial Thinking and Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond correlational evidence, there is evidence that spatial visualization has a causal effect on these numerical skills. Cognitive training studies have demonstrated transfer of gains from spatial visualization training (measured using spatial transformation tasks) to numerical competencies including: calculation performance (Cheng & Mix, 2014; Gilligan, Thomas, & Farran, 2019; Mix, Levine, Cheng, Stockton, & Bower, 2020); symbolic number comparison (Hawes, Moss, Caswell, Naqvi, & MacKinnon, 2017); word problems (Lowrie et al, 2019; Mix et al, 2020); and place value (Mix et al, 2020). For example, it has been found children who were trained in spatial transformation demonstrated significant improvements in accuracy on a range of number‐based measures including Missing Term Problems (Mix et al, 2020).…”
Section: Spatial Thinking and Mathematicsmentioning
confidence: 99%
“…value (Mix et al, 2020). For example, it has been found children who were trained in spatial transformation demonstrated significant improvements in accuracy on a range of number-based measures including Missing Term Problems (Mix et al, 2020). In short, several studies show that spatial transformation contributes causally to numerical skills.…”
mentioning
confidence: 99%
“…Beyond correlational evidence, there is evidence that spatial visualisation has a causal effect on these basic numerical skills. Cognitive training studies have demonstrated transfer of gains from spatial visualisation training to basic numerical competencies including: calculation performance (Cheng & Mix, 2014;Gilligan, Thomas, & Farran, 2019;Mix et al, 2020); symbolic number comparison (Hawes et al, 2017); word problems (Lowrie, Logan, & Hegarty, 2019;Mix et al, 2020) and place value (Mix et al, 2020). In short, several studies show that spatial visualisation contributes causally to basic numerical skills.…”
Section: Spatial Thinking and Mathematicsmentioning
confidence: 99%
“…Training on spatial tasks has indeed enhanced mathematical performance in some studies of rotation training (Hawes et al, 2017;Lowrie et al, 2017;Mix et al, 2020; but see also Hawes et al, 2015) as well as for vsWM (Bergman-Nutley and Klingberg, 2014;Berger et al, 2020;Mix et al, 2020;Judd and Klingberg, 2021; but see also Roberts et al, 2016). Mix et al (2020) recently compared children training on either vsWM or MR tasks and found that both groups improved compared to a control group engaged in language training. There was no significant difference between the two training groups in terms of the amount of improvement, nor on the type of mathematical tasks that were improved.…”
Section: Introductionmentioning
confidence: 98%
“…These correlations in performance have led to suggestions of enhancing mathematical ability through spatial training (Stieff and Uttal, 2015). Training on spatial tasks has indeed enhanced mathematical performance in some studies of rotation training (Hawes et al, 2017;Lowrie et al, 2017;Mix et al, 2020; but see also Hawes et al, 2015) as well as for vsWM (Bergman-Nutley and Klingberg, 2014;Berger et al, 2020;Mix et al, 2020;Judd and Klingberg, 2021; but see also Roberts et al, 2016). Mix et al (2020) recently compared children training on either vsWM or MR tasks and found that both groups improved compared to a control group engaged in language training.…”
Section: Introductionmentioning
confidence: 99%